Provenance analysis for submarine fan sandstones of Huangliu Formation, Dongfang 13 gas field in Yinggehai Basin, South China Sea - Yintao Huang; Guangqing Yao; Fengde Zhou (Kuwait Journal of Science)
The reservoir in the upper Miocene Huangliu Formation, in the Yinggehai Basin, is composed of submarine fan deposits with burial depths from 2600m to 3500m. This paper presents an integrated method in provenance analysis by using data of petrography, heavy mineral assemblages, and geochemical compositions. The analysis produced a number of key results. First, two provenances exist, one in the west and the other in the east. Second, the submarine fan sandstone exhibits low percentages of zircon, tourmaline and garnet, whereas the neritic sandbar rocks exhibit high percentages of zircon, tourmaline and leucoxene, and low percentages of magnetite and garnet. Third, the Chemical Index of Alteration (CIA) values and Rb/Sr ratios of the submarine fan sandstone indicate moderate weathering intensity in the source region. SiO2/Al2O3 ratios indicate moderate sediment maturity. Similar rare earth element patterns of the submarine fan sandstone samples from three wells indicate a common provenance. Th-Sc, Co/Th-La/Sc and REE patterns point to derivation from felsic source rocks. Fourth, the integrated method and comparison of REE patterns of the submarine fan sandstone with that of possible adjacent source rocks indicates that the submarine fan sandstone most probably derived from the western Kuntum uplift. It is concluded that the integration of petrological composition of the sandstone, the heavy mineral assemblage and major and trace elements geochemistry is useful for provenance identification.